CNS GNPDA2 Does Not Control Appetite, but Regulates Glucose Homeostasis - Gutierrez-Aguilar, Ruth; Grayson, Bernadette E.; Kim, Dong-Hoon; Yalamanchili, Suma; Calcagno, Mario L.; Woods, Stephen C.; Seeley, Randy J. (Frontiers in Nutrition, 2021)
GNPDA2 has been associated with human obesity and type-2 diabetes by using a GWAS approach. GNPDA2 is an enzyme involved in the hexosamine biosynthesis pathway, which is known to be important for nutrient sensing in various organism. Its counter enzyme, GFAT, has previously been shown to be important to the development of insulin resistance in diabetes. The implication of GNPDA2 and GFAT in metabolism is scarce and the effect of both enzymes over appetite and glucose homeostasis is unknown. Aim: Identify the role of GNPDA2 and GFAT in nutrient sensing circuits of the CNS that are important for the regulation of both appetite and glucose homeostasis. Methods: Using Long Evans rats, we administered either a GNPDA2 or GFAT antagonist or vehicle in i3vt. Key findings: GNPDA2 is highly expressed in hypothalamus and adipose tissue, followed by muscle and liver. GNPDA2 is expressed in different hypothalamic nuclei (ARC, DMH, LHA, PVN). GNPDA2 is downregulated in hypothalamus under diet-induced obesity (as previously described), but GFAT expression does not change. Moreover, i3vt infusion of GNPDA2 or GFAT inhibitor resulted in increased c-Fos in areas related to appetite and glucose homeostasis control as PVN and DMH and to a lesser extent in the LHA and ARC. Central inhibition of GNPDA2 does not alter either acute food intake or body weight; however, GFAT inhibition diminished appetite and body weight due to visceral illness. In addition, central administration of the GNPDA2 antagonist, prior to an intraperitoneal glucose tolerance test, resulted in glucose intolerance in comparison to vehicle without altering insulin levels. Significance: These results suggest that central GNPDA2 does not control appetite, but regulates glucose homeostasis.